The prevalence of COVID-19 among healthcare professionals at primary healthcare centers - Zayer, Raheem Hussein (South Asian Journal of Social Sciences and Humanities, 2023)
Background: The SARS-CoV-2 infection typically triggers discernible immunological responses  in most reported cases. Employing a serological test could identify prior asymptomatic infections  and aid in evaluating an individual's immune status. Given that healthcare professionals face a  higher risk of COVID-19 exposure, the utilization of personal protective equipment remains the  foremost approach in averting disease transmission within healthcare facilities. Objectives: To  ascertain the prevalence of COVID-19 among healthcare professionals working in primary  healthcare centers located within the AL-Sader city district. Method: During the period between  November 1st, 2020, and December 31st, 2020, a cross-sectional study was carried out in nine  primary healthcare centers, chosen through a cluster random sampling method. Result: Out of the  470 participants included in the study, 101 (21.5%) had a documented history of COVID-19  infection, with 76 confirmed through polymerase chain reaction analysis. Notably, a notable  correlation between a positive rapid immunological test result and a prior history of COVID-19  infection (p-value < 0.001). The rapid test showed a sensitivity of 56.6% and a specificity of  79.2%. Specifically, 125 participants (26.6%) tested positive using the rapid test, with 104 (83.2%)  exhibiting IgG antibodies, 5 (4%) displaying IgM, and 16 (12.8%) showing both IgG and IgM  antibodies. Conclusion: The prevalence of COVID-19 infection among participants exceeded the  anticipated levels. Significantly, there was a discernible correlation between positive rapid test  results and COVID-19 infection, as well as factors such as smoking, comorbidities, PPE training,  and household infections.
Keywords: COVID-19; prevalence; Healthcare; Iraqi; professionals